Perjumpaan Sebagai Jalan Pemenuhan “Aku” (Sebuah Tinjauan Teologis Praktis Pemikiran Yohanes Paulus II dan konsep Aku “ada-belum-penuh”) - Sutrimo, Kristinus (Borneo Review, 2024)
Abstract The focus of the discussion in the paper is Dialog in Encounter of the "I" Philosophy, a philosophical review of Armada Riyanto and John Paul II's thoughts on dialogue. The fact that the world is multidimensional is unavoidable. Within this plurality, for example, each religion has a claim of truth.Living together in society is a calling. Therefore, the presence of one human in the midst of another human must be a blessing. Every human being must have openness to each other, so that life together becomes more beautiful. However, it cannot be denied that in life together, every human being has his or her own freedom. It becomes a problem when humans abuse their freedom, causing conflict in the midst of life together. Every human being with all his circumstances also has freedom and will. This fact shows that humans need dialogue so that in life together they can respect and understand each other, so as to create a harmonious and peaceful life. The methodology used is literature study. Reading the thoughts of John Paul II from several documents, then having a dialogue with the concept of "I am not yet full" in Riyanto's Fleet Relationality philosophy. I discovered that there is no human being who has experienced fullness or perfection in himself. I am "not yet full" need a relationship with others, so that the empty part of me is filled and fulfilled. Encounters with others actually make one person more complete. Humans who have dialogue are humans who are headed for change and development.